Oncolytic adenovirus armed with IL-24 Inhibits the growth of breast cancer in vitro and in vivo - Wei Zhu; Lai Wei; Hongwei Zhang; Junxue Chen; Xinyu Qin (2012)
Abstract Background Interleukin-24 (IL-24) is a cytokine that belongs to the IL-10 family. It can selectively induce cancer cell apoptosis which has been utilized as a cancer gene therapy strategy. Methods A recombinant type five adenovirus containing IL-24 gene (designated CNHK600-IL24) was constructed, whose replication is activated only in tumor cells. The replication of CNHK600-IL24 in breast tumor cells and fibroblasts were assessed by TCID50 and MTT assay; the secretion of IL-24 was measured by ELISA and western blotting. The in vivo anti-tumor effect of CNHK600-IL24 was investigated in nude mice carrying orthotopic or metastatic breast tumor. Results We observed that CNHK600-IL24 could replicate efficiently and resulted in high level IL-24 expression and massive cell death in human breast cancer cell MDA-MB-231 but not in normal fibroblast cell MRC-5. In addition, orthotopic breast tumor growth in the nude mice model was significantly suppressed when CNHK600-IL24 was administered. In the metastatic model generated by tail vein injection, CNHK600-IL24 virotherapy significantly improved survival compared with the same virus expressing EGFP (median survival CNHK600-IL24, 55 days vs. CNHK600-EGFP, 41 day, p < 0.05 Mantal-Cox test). A similar phenomenon was observed in the metastatic model achieved by left ventricular injection as suggested by in vivo luminescence imaging of tumor growth. Conclusion The oncolytic adenovirus armed with IL-24, which exhibited enhanced anti-tumor activity and improved survival, is a promising candidate for virotherapy of breast cancer.